Potentiality of Payment for Ecosystem Services in Community Forest: Linking Upstream and Downstream Households - Ghimire, Pramod; Lamichhane, Uchita (Journal of Agriculture and Forestry University, 2025)
The characteristics of ecosystem services (ES) and developing a particular mechanism of sharing benefits generated from its uses among its contributors has become a matters of concerns to ecologists, environmentalist and economist. Payment for ecosystem services (PESs) is pursued as one mechanism which is increasingly used to sustain both the natural ecosystems and local livelihoods. A study was carried out in Nawalpur Saraswati-Basamadi Community Forest (NSBCF) in Makawanpur district to assess the potentiality for implementing PES mechanism. This study employed both qualitative and quantitative approaches. Households survey (n=142), key informant interview and focus group discussions were carried out to identify major environmental service and discuss the possibility of creating an institutional mechanism for PES. Discrete choice experiment (DCE) method was used to determine the preferences of both upstream and downstream communities for forest conservation. The study found provisioning, regulatory and cultural services (including forest products, pure and clean drinking water, tourism and recreation etc.) are the major ecosystem services provided by NSBCF and forest products; and pure and clean drinking water being the most important ecosystem services. Community forest was reported as most preferred institution to follow the PES mechanism and indirect payment mechanism got the highest preference among the respondents. Majority of people from both the upstream and downstream community around NSBCF has positive response for willingness to pay (WTP) and willingness to accept (WTA) for ecosystem services. They have strong WTP of NRS. 187.70 per year/HH and WTA of NRS 295.10 per year/HH for the conservation of forest. This shows that both the upstream and downstream communities are willing to conserve the forest and implement the PES mechanism as sustainable conservation approach. Therefore, this study recommends that there are adequate existing institutions at the local level that could play vital role in implementing PES mechanisms. For this the appropriate institution should be identified and their respective role should be fixed. Furthermore, capacity building and awareness program among the upstream and downstream user is essential for the successful implementation of PES mechanism.